Prescription drug spending by payer: Implications for managed care - Yousef Chavehpour; Rajesh Balkrishnan; Joel E. Segel (Elsevier, 2024)
Background: Brand-name prescription drugs are an important driver of prescription drug spending, but different payers may bear these costs differentially necessitating different policy goals for each payer. But little is known about how the top 10 selling drugs in the U.S. impact spending across payers. Objective: To estimate the differential spending burden of top prescription drugs on Medicaid, Medicare, commercial coverage, and out-of-pocket (OOP) spending. Methods: The percentage of total prescription drug spending, total spending, total prescriptions, and average cost per prescription overall and for each of the following payers - Medicaid, Medicare, private insurance, and OOP - was calculated for each of the top 10 selling prescription drugs using 2017-2019 Medical Expenditure Panel Survey data. Results: These 10 prescription drugs accounted for average annual spending of $83.4 billion and 19.0% of all prescription drug spending. Medicare tended to contribute the highest fraction of spending. The average annual cost per prescription ranged from $500 for Advair to $7400 for Tecfidera. Significant variation in the average annual number of prescriptions filled was observed, ranging from 1.4 million for Tecfidera to 13.6 million for Lantus. Conclusions: The findings highlight the significant impact of the top 10 selling prescription drugs on U.S. prescription drug spending. The wide variation in per prescription cost as well as contribution to each payer's prescription drug burden emphasizes how policies targeting top-selling drugs may differentially impact payers as well as how payer-specific policies may differ substantially even for top selling drugs.